A Tubular Polymer Redox Flow Battery with a Ceramic Membrane. Issue 2 (25th November 2016) - Stolze, Christian; Schmerbauch, Christoph; Friebe, Christian; Schubert, Ulrich S.
Abstract: A tubular cell design for redox flow batteries is introduced utilizing chemically, mechanically, and thermally stable ceramic membranes. The basic viability of this new cell design is demonstrated via static and pumped charge and discharge experiments with a laboratory prototype. Electrochemical impedance spectroscopy measurements are presented for the investigation of the internal Ohmic resistance. The technological benefits of a tubular cell design as well as its limitations are discussed. Abstract : Tubular cells : A novel, tubular cell design for redox flow batteries (RFBs) is introduced, allowing for the first time the utilization of a chemically, mechanically, and thermally stable ceramic membrane in an easy to upscale redox flow battery. Electrochemical impedance spectroscopy measurements are presented for the investigation of the internal Ohmic resistance. The technological benefits of a tubular cell design as well as its limitations are discussed.